The Readiness of the Level 3 Nursing Students of University of Luzon in Their Operating Room Experience - Flores, Joelle Shaine; Fernandez, Bernadeth; Canta, Heart Nicole; Peleglorio, Charllote; Cave, Liam Joshua; De Jesus, Christian; Beltran-Villar, Johanna (Celebes Nursing Journal, 2025)
Introduction: Operating rooms, often referred to as the "heart" of any hospital, demand a unique set of skills, knowledge, and personal attributes from healthcare professionals. Early exposure to healthcare settings is crucial for fostering student confidence and competence, providing them with the tools to manage complex patient situations. Studies show that early clinical exposure helps students enhance their communication, teamwork, and professional identity, giving them firsthand experience with patient care and the healthcare system. This exposure also fosters compassion and a deeper understanding of patient needs. Objective: The study aimed to assess the readiness of the 3rd year nursing students in the operating room, which covers knowledge, Skills, and Attitude (KSA). Method: The descriptive quantitative method was utilized in this study. The study limits its coverage to forty-two (42) 3rd year nursing students at the University of Luzon for the school year 2023-2024 only. Each student was given the same set of questionnaires distributed through an online survey. Results: Findings concluded that various preparation procedures, such as lectures accompanied by return demonstrations, have aided in the preparation of the students for their operating room experience. However, as novices in the operating room, most students lack the coping mechanisms. Clonclusion: stress management techniques needed to cope in the busy world of the operating room.